2002
DOI: 10.1007/s00259-001-0722-0
|View full text |Cite
|
Sign up to set email alerts
|

Dose selection for radioiodine therapy of borderline hyperthyroid patients with multifocal and disseminated autonomy on the basis of 99mTc-pertechnetate thyroid uptake

Abstract: The aim of this study was to optimise radioiodine therapy of diffuse and nodular toxic goitre by calculation of the radiation dose delivered to the thyroid on the basis of the pretreatment technetium-99m pertechnetate thyroid uptake under thyrotropin suppression (TcTU(s)). The TcTU(s) value serves as a substitute for the non-suppressible iodine turnover and the functional autonomous mass. Marinelli's formula was used to calculate tissue absorbed doses of 150 Gy, 200 Gy, 250 Gy and 300 Gy to the thyroids of 438… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
2
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 6 publications
2
24
2
4
Order By: Relevance
“…However, the continuous intake of iodised table salt could have reduced thyroid uptake of technetium-99m pertechnetate. This notion is supported by the fact that thyroid uptake of iodine directly correlates with technetium-99m pertechnetate uptake, 18 implying that the mode by which the two radiochemicals are taken up by the thyroid is similar. In an earlier study, Reinhardt et al 19 demonstrated that thyroid uptake of pertechnetate inversely correlated with iodine intake, suggesting that preloading the thyroid with cold iodine can significantly reduce the subsequent uptake of technetium-99m pertechnetate.…”
Section: Discussionsupporting
confidence: 61%
“…However, the continuous intake of iodised table salt could have reduced thyroid uptake of technetium-99m pertechnetate. This notion is supported by the fact that thyroid uptake of iodine directly correlates with technetium-99m pertechnetate uptake, 18 implying that the mode by which the two radiochemicals are taken up by the thyroid is similar. In an earlier study, Reinhardt et al 19 demonstrated that thyroid uptake of pertechnetate inversely correlated with iodine intake, suggesting that preloading the thyroid with cold iodine can significantly reduce the subsequent uptake of technetium-99m pertechnetate.…”
Section: Discussionsupporting
confidence: 61%
“…There are several possible explanations for and factors contributing to the higher incidence rate of hypothyroidism in our patients: First, the higher rate might be due to the longer follow‐up time in our study. When observation is limited to 12 months or less, as in several previous reports, 17,20,27 the overall hypothyroidism incidence rate of hypothyroidism may be lowered, as it increases with ongoing follow‐up time 15,19,21,25 . Second, pretreatment with antithyroid drugs is a possible confounder, because in case of stimulation of a previously suppressed TSH by antithyroid drugs, the risk of hypothyroidism may increase.…”
Section: Discussionmentioning
confidence: 95%
“…Third, hypothyroidism was defined as elevation of TSH above the normal range, including patients with subclinical hypothyroidism. Other previous studies failed to clearly define the criteria for hypothyroidism 17 or left patients with subclinical hypothyroidism untreated 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it may be prudent to use temporary antithyroid drug treatment to achieve euthyroidism, discontinue it for several days before and after 131 I administration, and then resume therapy to maintain normal thyroid function while waiting for the effect of the radioiodine, particularly in older patients and those with cardiac disease. 138,139 The incidence of postablative hypothyroidism after radioiodine therapy has been reported to be 25% to 50%, which is lower than that encountered after treatment of patients with Graves' disease. [116][117][118][119][120][121][122][123] One randomized controlled trial has also confirmed this effect of PTU in toxic multinodular goiter.…”
Section: Radioactive Iodinementioning
confidence: 99%